Exploring Engagement Repetoires in Social Media: the Museum Perspective - Linda Lotina; Krista Lepik (Journal of Ethnology and Folkloristics)
In our paper, we have developed a list of modes for audience engagement on social media on the basis of the Facebook posts of selected museums in Latvia and Estonia. Within the frame of our study, the museums’ Facebook posts covering a timespan of one year have been analysed using the method of close reading and applying the principles of grounded theory. A multi-dimensional approach to various modes of engagement is proposed in order to involve different visitors in the activities of the museum, and considering different functions of the message. The results of the paper are applicable when considering diverse repertoires for modes of engagement with the museum’s audiences on social media, as well as when engaging with them on-site. The paper contributes to the trend of democratisation within the museum context by exploring the potential of museums when forging their relationships with their visitors.